Developing the Coastal Area of Tanjung Riau's Old Village into a Decent and Productive Residence - Azis Burhan; Yuanita FD Sidabutar (Universitas KH. Abdul Chalim Mojokerto, 2025)
Batam is a city in the Riau Islands Province, Indonesia. Batam City comprises several islands: Batam, Galang, and Rempang, along with other smaller islands located in the Malacca and Singapore Straits. Three larger islands are connected by the Barelang Bridge: Batam, Galang, and Rempang. Batam City is part of the Batam-Bintan-Karimun (BBK) Free Trade Zone. Batam City covers a land area of ​​715 km², consisting of rice fields, forests, and hills, while its sea area covers 1,575 km². The city's climate is tropical, with temperatures ranging from 25 to 35 degrees Celsius, and the land surface is varied, with valleys and hilly areas. Kampung Tua Tanjung Riau is a sub-district located in the Sekupang district of Batam City, Riau Islands, Indonesia. The sub-district covers an area of ​​23.90 km², with a population of 23,987 in 2020, and a density of 1,004 people per km². Kampung Tua Tanjung Riau is located in neighborhood units (RW) 01 and 02. In densely populated areas like Kampung Tua Tanjung Riau, environmental issues arise, such as uncontrolled waste management. Some homes still dispose of toilet waste into the sea, creating environmental problems. The public must become aware of tourism, which can boost economic growth in the area. However, several obstacles must be addressed immediately by local residents and the government to provide support for residents' prosperity and a healthy environment.